2023
DOI: 10.1186/s12889-023-15225-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary approaches to stop hypertension (DASH)-style diet in association with gastroesophageal reflux disease in adolescents

Abstract: Background Dietary patterns and food items have been associated with gastroesophageal reflux disease (GERD) risk and they have led to conflicting findings. The aim of this study was to determine the association between a dietary approach to stop hypertension (DASH)-style diet with the risk of GERD and its symptoms in adolescents. Study design Cross-sectional. Methods This study was performed on 5,141 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Fiber-rich foods, like whole grains, fruits, and vegetables, aid in proper bowel movements and prevent constipation [124], which can contribute to GERD symptoms [58,125] Papaya contains enzymes such as papain that aid digestion and help break down proteins [126,127]. Eating ripe papaya or drinking papaya juice can support healthy digestion [127] and reduce symptoms of GERD [116].…”
Section: Enhancing Digestive Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fiber-rich foods, like whole grains, fruits, and vegetables, aid in proper bowel movements and prevent constipation [124], which can contribute to GERD symptoms [58,125] Papaya contains enzymes such as papain that aid digestion and help break down proteins [126,127]. Eating ripe papaya or drinking papaya juice can support healthy digestion [127] and reduce symptoms of GERD [116].…”
Section: Enhancing Digestive Functionmentioning
confidence: 99%
“…GERD management entails the avoidance of trigger foods like spicy food, citrus fruits, tomatoes, onions, garlic, chocolate, mint, caffeinated beverages, alcohol, and carbonated drinks [ 50 ], prioritizing the consumption of lean proteins and emphasizing the intake of whole grains and fiber-rich foods like oatmeal and brown rice instead [ 6 , 58 ]. In one study, individuals with the highest intake of fruits and vegetables demonstrated a 33% lower risk of developing GERD [ 59 ].…”
Section: Gerd Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Additionally, the DASH diet was protective against gastroesophageal reflux disease. 22 In Brazil, among a large adolescent sample (n = 71,553), no association was found between arterial hypertension or overweight/obesity and the DASH diet. 23,24 The MIND diet was designed for aging populations to improve brain health and is associated with a lower risk of all-cause mortality over 12 years, 25 slower cognitive decline, 8 decreased severity of anxiety disorders, 26 and reduced risk of Alzheimer's disease 27 and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 96%